Literatur Review: Gambaran Karakteristik Ibu dengan Persalinan Sectio Caesarea (SC) - Suliswanti, Suliswanti; Endang Surani (Journal of Medical Practice and Research, 2026)
Cesarean section has become one of the most frequently performed obstetric procedures worldwide and reflects complex interactions between maternal characteristics, reproductive history, and clinical conditions that emerge during pregnancy and childbirth. This study aimed to analyze the profile of mothers undergoing cesarean delivery through a descriptive literature review of scientific publications and national health reports. Relevant literature was obtained from reputable academic databases and official health documents to identify consistent patterns in maternal characteristics associated with cesarean delivery. The synthesis indicates that demographic attributes such as maternal age, education level, and socioeconomic conditions shape access to healthcare services and influence patterns of delivery management. Obstetric history, including parity, gestational age, and previous delivery experiences, also contributes to variations in delivery pathways and clinical decision-making. In addition, several medical indications, including hypertensive disorders of pregnancy, fetal distress, and other obstetric complications, represent important determinants underlying the performance of cesarean procedures. These interconnected factors demonstrate that cesarean delivery reflects not only clinical necessity but also broader maternal health profiles within healthcare systems. Understanding these multidimensional characteristics provides an important foundation for strengthening maternal health strategies and improving evidence-based obstetric care.